Intraoperative Techniques for the Plastic Surgeon to Improve Pain Control in Breast Surgery. Issue 11 (November 2017) - Farias-Eisner, Gina; Kao, Kenneth; Pan, Judy; Festekjian, Jaco; Gassman, Andrew
Abstract : Summary: In recent years, there has been a growing emphasis placed on reducing length of hospital stay and health costs associated with breast surgery. Adequate pain control is an essential component of enhanced recovery after surgery. Postoperative pain management strategies include use of narcotic analgesia, non-narcotic analgesia, and local anesthetics. However, these forms of pain control have relatively brief durations of action and multiple-associated side effects. Intraoperative regional blocks have been effectively utilized in other areas of surgery but have been understudied in breast surgery. The aim of this article was to review various intraoperative techniques for regional anesthesia and local pain control in breast surgery and to highlight areas of future technique development. Abstract : Supplemental Digital Content is available in the text.